1997
DOI: 10.1300/j091v07n01_05
|View full text |Cite
|
Sign up to set email alerts
|

Clearcut Harvesting and Structural Dynamics of a Boreal Forest in Saskatchewan

Abstract: The conversion of natural forests into managed forests raises concerns about sustained timber production and nature conservation. This study combined long-term inventory projections for some 84,000 ha of productive boreal mixedwood in Saskatchewan with fragmentation analysis. A spatially unrestricted clearcut harvesting regime was simulated for a 100-year period .The current harvest rates of 1.5 m3 ha-' per year could be sustained, but the age class distribution of the forest would markedly shift towards young… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…White and Mladenhoff (1994) compared original land grant survey reports with current forest inventories of Wisconsin and concluded that agricultural settlement dramatically increased the area of young forests and cold-temperate northern (i.e., boreal) species, at the expense of the cool-temperate old-growth eastern hemlock forests. Langen and Bouman (1998) showed that technologically advanced wood harvesting systems and plantation silviculture rapidly changed the structure of cold-tem-perate forests in Saskatchewan. Socio-cultural organization expressed in forest ownership patterns also had an apparent influence on forest structure.…”
Section: Introductionmentioning
confidence: 99%
“…White and Mladenhoff (1994) compared original land grant survey reports with current forest inventories of Wisconsin and concluded that agricultural settlement dramatically increased the area of young forests and cold-temperate northern (i.e., boreal) species, at the expense of the cool-temperate old-growth eastern hemlock forests. Langen and Bouman (1998) showed that technologically advanced wood harvesting systems and plantation silviculture rapidly changed the structure of cold-tem-perate forests in Saskatchewan. Socio-cultural organization expressed in forest ownership patterns also had an apparent influence on forest structure.…”
Section: Introductionmentioning
confidence: 99%